2020
DOI: 10.1021/acsami.0c16543
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reaction-Induced Defect Engineering: Enhanced Visible and Near-Infrared Absorption of Wide Band Gap Metal Oxides with Abundant Oxygen Vacancies

Abstract: Modified metal oxides with narrow band gaps have attracted great interest in photothermal applications because of their wide optical absorption range. To tune wide band gap metal oxides into visible and near-infrared responsive materials, we deploy a unique interfacial reaction-induced defect engineering approach, which enables us to effectively modify the electronic structure of metal oxides by introducing oxygen vacancy defects. This approach reduced the band gap of zirconia from 5.47 to 1.38 eV, accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Under this circumstance, the observed blackening phenomenon of ZrO 2 is reasonably attributed to the interfacial reaction between ZrO 2 and Ti, which is in line with our previous report. [ 24 ] In addition to the formation of reaction layers adjacent to the ceramic substrate, the Ti substrate is dissolved into liquid filler to form the Ti x (Cu, Pd) y compounds and α‐Ti + Ti 2 Pd phases nearby the titanium alloy. Additionally, the formation of the above chemical compounds in the brazing joint ensures the high‐quality metallurgical bonding of ZrO 2 /Ti brazing joints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this circumstance, the observed blackening phenomenon of ZrO 2 is reasonably attributed to the interfacial reaction between ZrO 2 and Ti, which is in line with our previous report. [ 24 ] In addition to the formation of reaction layers adjacent to the ceramic substrate, the Ti substrate is dissolved into liquid filler to form the Ti x (Cu, Pd) y compounds and α‐Ti + Ti 2 Pd phases nearby the titanium alloy. Additionally, the formation of the above chemical compounds in the brazing joint ensures the high‐quality metallurgical bonding of ZrO 2 /Ti brazing joints.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that there are two important steps in the interfacial reaction process (Figure 5b), which are oxygen dissolved in titanium and oxygen diffusion in ZrO 2 . [24] To implement these two steps, a well-contacted ZrO 2 /Ti interface and a high-temperature environment are necessary. Compared to the previous method of preparing nano-sized black ZrO 2 at relatively low temperature, [18,22] the high temperature employed in this method greatly accelerates the diffusion of oxygen ions in ZrO 2 , leading to the preparation of black ZrO 2 with large sizes.…”
Section: Blackening Of Zro 2 After Active Metal Brazingmentioning
confidence: 99%
“…S3 , the band gap of the WTM-900 was 3.05 eV. On the other hand, the BTM-900 displayed two-part of the slope, in which the relatively small band gap energy of 2.82 eV is ascribed to the intermediate band formed below the conduction band and the large band gap of 3.22 eV is attributed to the intrinsic band gap of TiO 2 [25] , [31] , [32] , [33] . The photoluminescence (PL) spectrum of BTM-900, shown in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Strategies to ameliorate photocatalytic ZrO 2 activity, can include: (i) heteroatom insertion 12 17 into ZrO 2 crystal, or (ii) Oxygen-defects’ creation 18 23 . The influence of heteroatoms in ZrO 2 has been investigated 12 17 , in photocatalytic dye degradation or O 2 evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Without heteroatom doping, generation of reduced states in reducible metal-oxides, such as TiO 2 , are decisively beneficial for H 2 photo yield. Examples include the work of Mao et al 23 , Naldoni et al 26 and our Flame Spray Pyrolysis (FSP)-made black TiO 2−x 27 . ZrO 2 is a notoriously non-reducible oxide 28 , 29 , since introduction of Vo’s into the ZrO 2 lattice is not favored energetically 8 , 15 20 , thus specific synthesis methods are needed to achieve reduction of the ZrO 2 lattice.…”
Section: Introductionmentioning
confidence: 99%